Cross-satellite calibration of high-energy electron fluxes measured by FengYun-4A based on Arase observations - XiaoYu Wang; Xing Cao; Xin Ma; XiaoXin Zhang; AnQin Chen; JunHu Dong; BinBin Ni; XianKang Dou (Earth and Planetary Physics, 2023)
We use the High-energy Electron Experiments (HEP) instrument onboard Arase (ERG) to conduct an energy-dependent cross-satellite calibration of electron fluxes measured by the High Energy Particle Detector (HEPD) onboard FengYun-4A (FY-4A) spanning from April 1, 2017, to September 30, 2019. By tracing the two-dimensional magnetic positions (L, magnetic local time [MLT]) of FY-4A at each time, we compare the datasets of the conjugate electron fluxes over the range of 245–894 keV in 6 energy channels for the satellite pair within different sets of L × MLT. The variations in the electron fluxes observed by FY-4A generally agree with the Arase measurements, and the percentages of the ratios of electron flux conjunctions within a factor of 2 are larger than 50%. Compared with Arase, FY-4A systematically overestimates electron fluxes at all 6 energy channels, with the corresponding calibration factors ranging from 0.67 to 0.81. After the cross-satellite calibration, the electron flux conjunctions between FY-4A and Arase show better agreement, with much smaller normalized root mean square errors. Our results provide a valuable reference for the application of FY-4A high-energy electron datasets to in-depth investigations of the Earth’s radiation belt electron dynamics.